An approach to develop haptic feedback control reference for steering systems using open-loop driving manoeuvres. Issue 12 (1st December 2020) - Chugh, T.; Bruzelius, F.; Klomp, M.; Shyrokau, B.
Abstract: In this paper, a methodology to capture the model-based haptic feedback control reference for closed-loop steering systems is demonstrated. The parameterisation is based on the measurements of open-loop driving manoeuvres for the inertia-spring-damper-friction reference model. The steady-state and transient manoeuvres are used to identify the model parameters. The reference model is limited to the haptic feedback of driver excitation in the linear vehicle handling range and intended to be used in closed-loop steering control strategies. The model parameters have an intuitive interpretation that allows to be used in both admittance and impedance control setting. The feasibility of the proposed model is demonstrated in a validated simulation environment for electric power assisted steering and on a real hardware for the steer-by-wire force-feedback case.